2016
DOI: 10.18552/2016/scmt4s207
|View full text |Cite
|
Sign up to set email alerts
|

Urban Highway Life Cycle Assessment and Data Collection Methodology

Abstract: Life cycle assessment (LCA) of using recycled materials in roadways is currently not well-understood or documented. A research team from the Recycled Materials Resource Center (RMRC) analyzed the use of recycled materials in the reconstruction of the Beltline Highway in Madison, Wisconsin, to assess quantitatively and accurately the environmental and economic benefits of sustainable road construction. Recycled materials used in the reconstruction and expansion of an urban, 2.4 kilometer (1.5 mile) stretch of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…They also noticed that, in the case of Hot Mix Asphalt Recycling (HMAR)-the worst-case scenario between technologies-the addition of 30% and 50% RAP reduced the environmental indices. Bloom et al [29] carried out LCAs on recycled materials used for the reconstruction of a highway, converting the HMA to rigid pavement. These materials were fly ash, steel slag, RCA, RAS, and RAP.…”
Section: Introductionmentioning
confidence: 99%
“…They also noticed that, in the case of Hot Mix Asphalt Recycling (HMAR)-the worst-case scenario between technologies-the addition of 30% and 50% RAP reduced the environmental indices. Bloom et al [29] carried out LCAs on recycled materials used for the reconstruction of a highway, converting the HMA to rigid pavement. These materials were fly ash, steel slag, RCA, RAS, and RAP.…”
Section: Introductionmentioning
confidence: 99%
“…Turk et al [6] and Bloom et al [7] also explored the partial and complete replacement of natural aggregate base course with recycled construction waste (RCW) to varying degrees of GHG reduction. Bloom, Canton, Ahlman and Edil [7] assessed the environmental benefits of RAP usage during the M&R stages of asphalt pavements in their United-States-based study. The authors employed a 4% replacement of the asphalt binder content by RAP and observed a significant reduction in GHG emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The actual design including RAP was compared with a reference design using only virgin materials to evaluate the reduction in environmental impacts. Results indicated that the use of the recycled materials reduced impacts in most environmental aspects, including energy consumption (15–25% reduction) and CO 2 emissions (17–24% reduction) ( 20 ). Similarly, Zaumanis et al conducted an environmental effect and cost calculation for using 100% RAP mix and demonstrated reduction of emission by 35% while reducing the costs of materials by half ( 21 ).…”
Section: Introductionmentioning
confidence: 99%